Passage through Armageddon : the russians in war and revolution 1914-1918 - Lincoln, W. Bruce (Oxford : Oxford University Press, 1994)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Nicolaas II; Russische revolutie; Sovjet-Unie.; Rusland